1996
DOI: 10.1128/jb.178.8.2178-2185.1996
|View full text |Cite
|
Sign up to set email alerts
|

Proton motive force generation by citrolactic fermentation in Leuconostoc mesenteroides

Abstract: In Leuconostoc mesenteroides subsp. mesenteroides 19D, citrate is transported by a secondary citrate carrier (CitP). Previous studies of the kinetics and mechanism of CitP performed in membrane vesicles of L. mesenteroides showed that CitP catalyzes divalent citrate Hcit In bacteria, metabolic energy present in the form of ATP and ion gradients of H ϩ and Na ϩ are used to drive various endergonic reactions associated with cellular growth. The two forms of metabolic energy can be interconverted by the action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 22 publications
3
98
2
1
Order By: Relevance
“…In addition, the increased levels of glucose and lactate in the urine from treated animals are consistent with mitochondrial impairment; this proposed inability may result from a lack of acetylCoA in the mitochondria as a result of a reduction in the rate of oxidative phosphorylation and fatty acid β-oxidation (McGarry and Foster, 1980). These results provided evidence for the assumption that the cells switched to gluconeogenesis and glycolysis to compensate for the loss of ATP coming from fatty acid β-oxidation (Marty-Teysset et al, 1996). Our clinical chemistry data and liver histopathology examination could support it also.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the increased levels of glucose and lactate in the urine from treated animals are consistent with mitochondrial impairment; this proposed inability may result from a lack of acetylCoA in the mitochondria as a result of a reduction in the rate of oxidative phosphorylation and fatty acid β-oxidation (McGarry and Foster, 1980). These results provided evidence for the assumption that the cells switched to gluconeogenesis and glycolysis to compensate for the loss of ATP coming from fatty acid β-oxidation (Marty-Teysset et al, 1996). Our clinical chemistry data and liver histopathology examination could support it also.…”
Section: Discussionsupporting
confidence: 61%
“…Lactic acid bacteria in the phylum Firmicutes are facultative anaerobic bacteria that cannot grow on citrate as the sole source of carbon and energy, but many species are known to ferment citrate in cometabolism with a carbohydrate. The citrolactic fermentation pathway, like the malolactic fermentation pathway, is a secondary metabolic energy-generating route that produces proton motive force (96). The transporter involved in the uptake of citrate from the medium is the citrate/lactate exchanger, CitP, of the 2HCT transporter family.…”
Section: Physiological Functionmentioning
confidence: 99%
“…In the exchange mode, the proton is believed to go back and forth during transport. The precursor/product exchangers are symporters that were optimized to catalyze exchange, which is their physiological function; exchange is much faster than symport (see also "Kinetics" in "MECHANISMS" below) (7,94,96,107). Exchangers such as CitP and MleP recognize structurally related compounds; citrate and lactate, and malate and lactate, are pairs of 2-hydroxycarboxylates, HO-CR 2 -COO Ϫ , that differ in the R groups.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…This finding could be explained by the fact that citric acid (Lutgens and Gottschalk 1980;Marty-Teysset et al 1996), malic acid (Renault et al 1988;Loubiere et al 1992) and fumaric acid (Tran et al 1997;Tielens and Van Hellemond 1998) may positively modulate the energy metabolism of some bacterial strains usually residing in the hindgut. Lopez et al (1999) observed that sodium fumarate at 5 and 10 mmol L -1 was able to stimulate ruminal proliferation of cellulolytic bacteria and digestion of fiber.…”
Section: Discussionmentioning
confidence: 99%